In the crisis of comparative literature and its cognitive and methodological sources (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The impact of the "crisis of comparative literature" (Renee Wilk) in the critical center of the fire spread in the wild, although the vocabulary did not bear new added to the efforts of critics and comparison in his time and before. From a researcher dealing with the issues of comparative literature only pointed out a statement or hint To what Wilk discussed in his crisis. The pages of this research may be able to capture the knowledge and methodology of WELC in formulating the points presented in its crisis, relying on extrapolation and devising a means, and a tool for the fairness of the previous efforts objectively and impartially, And its objectives.